2007
DOI: 10.1021/jf070440a
|View full text |Cite
|
Sign up to set email alerts
|

Direct in vivo Evidence of Protective Effects of Grape Seed Procyanidin Fractions and Other Antioxidants against Ethanol-Induced Oxidative DNA Damage in Mouse Brain Cells

Abstract: Ethanol is a principle ingredient of alcoholic beverages with potential neurotoxicity and carcinogenicity, and the ethanol-associated oxidative DNA damage in the central nervous system is well documented. The present work studied the possible protective effects of grape seed oligomer and polymer procyanidin fractions against ethanol-induced toxicity and compared these with resveratrol and other well-known antioxidants (ascorbic acid and vitamin E). By using the single cell gel electrophoresis (comet assay), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 47 publications
2
51
2
1
Order By: Relevance
“…FPR1 is a membrane receptor overexpressed in U87 cells, regulates the cell growth, survival, migration and invasion (11,12). Moreover, an in vivo study showed that repeated administration of F2 to mice had no adverse effects (13). These data suggest that F2 may serve as a safe and efficient antitumor agent.…”
Section: Introductionmentioning
confidence: 73%
“…FPR1 is a membrane receptor overexpressed in U87 cells, regulates the cell growth, survival, migration and invasion (11,12). Moreover, an in vivo study showed that repeated administration of F2 to mice had no adverse effects (13). These data suggest that F2 may serve as a safe and efficient antitumor agent.…”
Section: Introductionmentioning
confidence: 73%
“…There are previous works on daily systemic treatment with this antioxidant at a dose of 2350 mg/kg in monkeys to prevent toxicity. A recent publication demonstrated that a high dosage of tocopherol (100, 200, and 400 mg/kg) presented protective effects on ethanol-induced brain damage in mice (Guo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…After processing, large amounts of grape seeds were produced as side product, so grape seeds were believed to be an alternative cheap source of proteins (Zhou et al, 2010). Grape seeds account for about 2-3% of the whole grape berry, and have received increasing attention for its significant health and other benefits (Del Bas et al, 2005;Al-Awwadi et al, 2005;Guo et al, 2007;Terra et al, 2007). Many studies mainly focus on the polyphenols of grape seeds (Nuno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%